2022
DOI: 10.3390/cells11152318
|View full text |Cite
|
Sign up to set email alerts
|

The Loss-Function of the Male Sterile Gene ZmMs33/ZmGPAT6 Results in Severely Oxidative Stress and Metabolic Disorder in Maize Anthers

Abstract: In plants, oxidative stress and metabolic reprogramming frequently induce male sterility, however our knowledge of the underlying molecular mechanism is far from complete. Here, a maize genic male-sterility (GMS) mutant (ms33-6038) with a loss-of-function of the ZmMs33 gene encoding glycerol-3-phosphate acyltransferase 6 (GPAT6) displayed severe deficiencies in the development of a four-layer anther wall and microspores and excessive reactive oxygen species (ROS) content in anthers. In ms33-6038 anthers, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Type I exhibits absent anther cuticle and thinner exine compared with WT. Most of GMS mutants belong to this type and include ms25‐6065 (Zhang et al ., 2021 ), ms33‐6038 (Li et al ., 2022 ; Xie et al ., 2018 ; Zhu et al ., 2019 , 2020 ), ms30‐6028 (An et al ., 2019 ) and apv1 (Somaratne et al ., 2017 ) in maize and dpw (Shi et al ., 2011 ), gpat3 (Men et al ., 2017 ), cyp703a3–2 (Yang et al ., 2014 ) and tdr (Li et al ., 2006 ) in rice. Type II contains rice myb80 / bm1 (Xiang et al ., 2020 ), tip3 (Yang et al ., 2019 ) and pksb (this study) mutants that display denser anther cuticle but thinner exine compared with their WT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I exhibits absent anther cuticle and thinner exine compared with WT. Most of GMS mutants belong to this type and include ms25‐6065 (Zhang et al ., 2021 ), ms33‐6038 (Li et al ., 2022 ; Xie et al ., 2018 ; Zhu et al ., 2019 , 2020 ), ms30‐6028 (An et al ., 2019 ) and apv1 (Somaratne et al ., 2017 ) in maize and dpw (Shi et al ., 2011 ), gpat3 (Men et al ., 2017 ), cyp703a3–2 (Yang et al ., 2014 ) and tdr (Li et al ., 2006 ) in rice. Type II contains rice myb80 / bm1 (Xiang et al ., 2020 ), tip3 (Yang et al ., 2019 ) and pksb (this study) mutants that display denser anther cuticle but thinner exine compared with their WT.…”
Section: Discussionmentioning
confidence: 99%
“…ZmMs30 in maize encoding a GDSL lipase is required for pollen exine and anther cuticle formation (An et al ., 2019 ). On the contrary, many lipid‐metabolic GMS genes primarily involved in cutin and/or wax biosynthesis also take part in sporopollenin biosynthesis, for example OsGPAT3 in rice and ZmMs33 in maize encoding glycerol‐3‐phosphate acyltransferases (GPAT; Li et al ., 2022 ; Men et al ., 2017 ; Xie et al ., 2018 ; Zhu et al ., 2019 , 2020 ), rice Wax‐deficient anther1 (Os WDA1 ) encoding an aldehyde decarbonylase (Jung et al ., 2006 ) and rice OsABCG26 encoding an ATP binding cassette transporter G26 (Zhao et al ., 2015 ). However, how plants balance the distribution of these lipids and their derivatives in anthers and whether a lipid‐metabolic trade‐off between anther cuticle and pollen exine formation exists to promote their normal development and male fertility remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The function of GPAT genes under abiotic stresses such as drought, salinity, low temperature, and high temperature has been studied in many plants [ 33 , 34 , 36 , 37 , 38 , 40 , 41 , 43 , 53 ]. It is reported that the overexpression of the AtS1 gene improves the tolerance of Arabidopsis seedlings to low temperature stress, while the transformation of the squash GPAT gene into tobacco leads to a reduction in low temperature tolerance [ 31 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the network remains unclear in maize due to the relatively fewer characterized lipid metabolic GMS genes. Of maize lipid metabolic GMS genes, nine are involved in lipid biosynthesis, such as ZmMs20/IRREGULAR POLLEN EXINE1 ( ZmIPE1 ) (Chen et al ., 2017 ; Wang et al ., 2019 ), ZmMs25/ZmMs6021 (Tian et al ., 2017 ; Zhang et al ., 2021 ), ZmMs26 (Djukanovic et al ., 2013 ; Singh et al ., 2017 ), ZmMs30 (An et al ., 2019 ), ZmMs33 (Li et al ., 2022 , 2023 ; Xie et al ., 2018 ; Zhang et al ., 2018b ; Zhu et al ., 2019 , 2020 ), ZmMs45 (Cigan et al ., 2001 ), ABNORMAL POLLEN VACUOLATION1 ( ZmAPV1 ) (Somaratne et al ., 2017 ), ZmIPE2 (Huo et al ., 2020 ) and POLYKETIDE SYNTHASE B ( ZmPKSB ) (Liu et al ., 2022 ). The rest encode lipid transfer proteins or ABCG transporters that are involved in lipid transport in maize anther (Fang et al ., 2023 ; Wu et al ., 2022 ), including ZmMs2/ZmABCG26 (Choi et al ., 2011 ; Jiang et al ., 2021b ; Xu et al ., 2021 ), ZmMs13/ZmABCG2a (Fang et al ., 2022 ) and ZmMs44 (Fox et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%